산화스트레스로 인한 C6 Glioma Cell Apoptosis에 대한 길경의 세포보호효과 - 조재준(Jae Joon Jo); 신민구(Min Gu Shin); 김의수(Eui Su Kim); 이영수(Young Su Lee); 신용진(Yong Jin Shin); 전상윤(Sang Yun Jeon) (동의생리병리학회지, 2014)
This study is designed to investigate cytoprotective effects of Platycodon grandiflorus (Jacq.) A.DC on C6 glioma cell apoptosis by oxidative stress. Experimental C6 glioma cells were classified into four groups as follows: normal group, PGE group, chemical groups, PGE+chemical groups. Oxidative stress that caused by chemicals in the C6 glioma cell, check the impact to Chemical group was administered normal group. Apoptotic effect protecting in order to observe the chemical group was administered PGE. We to observe effects of PGE on SOD inhibition, total glutathione production in C6 glioma cells were administered PGE. In case of administration PGE, apoptosis induced by Paraquat was significantly decreased. In case of administration PGE, apoptosis induced by SNP was significantly decreased. In case of administration PGE, apoptosis induced by $H_2O_2$ was significantly decreased. In case of administration PGE, apoptosis induced by Rotenone was decreased, but the statistical significance was not. In case of administration PGE, SOD inhibition activities significantly decreased. In case of administration PGE, Total glutathione did not affect the content. These results suggest that PGE is able to treat a disease caused by oxidative stress and prevent a aging. These results suggest that PGE is a disease caused by oxidative stress and aging, the prevention and treatment of food shall be able to be applied.